The A STAKEHOLDER MANAGEMENT CONCEPTUAL FRAMEWORK - Sunita , Parveen Kumar Garg (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
In this study, concepts of stakeholder analysis and stakeholder management have been introduced and evaluated the management of stakeholders’ relationships in stakeholder theory framework in Turkish forestry practices. In accordance with this purpose especially General Directory of Forestry (GDF) and their applications were investigated in respect of stakeholder management strategies in Turkey. Some literature examples have given related to forest stakeholder analysis within the scope of stakeholder theory. Finally, stakeholder analysis and management studies have considered in Turkish forestry. There are offered a set of suggestions in the context of stakeholder theory for the future research.